Very High Incidence of Type 1 Diabetes Among Children Aged Under 15 Years in Tlemcen, Northwest Algeria (2015-2018) - Sarra Khater; Ammaria Aouar; Nawel Bensmain; Salih Bendedouche; Nafissa Chabni; Houari Hamdaoui; Abdellatif Moussouni; Zakarya Moqaddem (Galenos Yayincilik, 2021)
Objective:In Algeria, there is a lack of epidemiological data concerning childhood type 1 diabetes (T1D). The International Diabetes Federation estimated in 2019 that Algeria ranked 7th among countries with the highest prevalence of T1D. This study aimed to determine the incidence of T1D in children <15 years, living in Tlemcen in Northwest Algeria.Methods:A retrospective study using data from children (<15 years) who have been diagnosed with T1D in Tlemcen between 2015 and 2018, using the two-source capture-recapture method to estimate the completeness of ascertainment (%). Total average incidences, by sex, by onset age group, and by season of onset were calculated per 100,000 and per year.Results:During the study period, 437 new cases of T1D were registered, among them, 233 boys and 204 girls, with a sex ratio of 1.14. The average annual incidence rate of childhood T1D was 38.5/100,000 with a 95% confidence interval (CI): 35.20-41.79; boys: 40.51, 95% CI: 38.16-42.85; girls: 36.49, 95% CI: 34.17-38.80. Overall incidence rates in 2015, 2016, 2017 and 2018 were respectively 36.6 (95% CI: 33.72-39.48), 38.7 (95% CI: 35.43-41.97), 39.3 (95% CI: 35.97-42.62) and 39.5 (95% CI: 36.12-42.87)/100,000. Newly diagnosed children were more likely to present in winter and autumn. Ketoacidosis at diagnosis was diagnosed in 29.2%.Conclusion:The mean incidence of childhood T1D in Tlemcen was 38.5/100,000, this incidence is in the "extremely high" category of the World Health Organization DiaMond project classification of diabetes giving this region a very high risk.